Obtención de inhibidores de la Dipeptidil Peptidasa-IV del grano de Amaranto (Amaranthus hypochondriacus L.) y su efecto en la Glucemia de ratones Diabéticos - Reyes Bautista, Raúl (Universidad Autónoma Metropolitana, 2017)
Amaranth (Amaranthus hypochondriacus L), is a pseudocereal that shows protein content between 16-20%, this protein content is higher than the one found in most common cereals. Because of its remarkable protein content, amaranth has been subjected to several studies to find encrypted peptide sequences that may possess biological activities. However, just a few bioactive amaranth peptides have been identified and characterized. Some in silico and in vitro experiments have shown that these encrypted peptide sequences in the amaranth protein fraction are bioactive molecules with activities such as: antithrombotic, antihypertensive, anticarcinogenic, antioxidant, antiglycemic, among others. The antiglycemic property of amaranth peptides is related with the ability of these bioactive peptides to act as an inhibitor of the dipeptidyl peptidase IV (DPP-IV) enzyme. This enzyme is heavily involved in the postprandial glycemic regulation in humans. Considering the pharmacological potential of hydrolyzed amaranth peptides with biological activity, the objective of this work was: (a) to test, in vitro and in vivo, the ability of different amaranth peptides, derived from the hydrolysis of amaranth, to inhibit the enzymatic activity of DPP-IV; (b) to clarify the mechanism of inhibition of DPP-IV by these amaranth peptides; (c) to characterize and partially purify these hydrolyzed peptides by gel filtration chromatography; (d) to identify the relationship between amaranth peptides inhibitory effect and their relative molecular mass; and finally (e) to test the biological activity of hydrolyzed amaranth peptides in an in vivo system, by administration of the hydrolysed amaranth protein extracts to STZ-induced diabetic mice, and evaluation of glucose tolerance, insulin and glucagon concentrations. Four protein fractions were found in the amaranth seeds. The three main fractions were: Alb1 46%, Glu 22% and Glo 12%. An additional minor fraction was identified as Pro (<1%). These protein fractions made up to 83% of the total protein found in the amaranth seeds analyzed. Enzymatic hydrolysis of amaranth protein by using alcalase was extensive, however, the Glu fraction was easily hydrolysed, this fraction showed a degree of hydrolysis of 75 ± 0.92% at 24 h. On the other hand, Alb1 was highly resistant to the alcalase activity. This fraction required a E/S= 0.8 AU/g and showed a degree of hydrolysis of 43 ± 0.34% at 48 h. SDSprotein profiles indicated that the hydrolysis of the different amaranth protein fractions was faster and more effective on the proteins having a higher molecular mass when the enzymatic hydrolysis by alcalase was used. Conversely, proteins showing a molecular mass between 2024 kDa were more resistant to the alcalase activity. After 24 h of hydrolysis, the fraction with the best capacity to inhibit DPP-IV was Glu (85  0.2%), meanwhile, Alb1 and Glo showed an inhibitory effect of 45  0.2% and 63  0.5%, respectively, after 48 h of hydrolysis. The hydrolyzed amaranth protein extracts that showed the highest inhibition capacities were partially purified by molecular exclusion chromatography. It was found that peptides having a molecular mass of 0.86, 0.65 and 0.45 kDa, isolated from the fractions Alb1, Glo and Glu, respectively, were more effective to inhibit DPP-IV in the in vitro experiments. The IC50 for the Alb1, Glo and Glu peptides were 1.98  0.01, 0.25  0.04 and 0.12  0.006 mg/mL, respectively. Based on these results it was found that there was an inverse relationship between molecular mass and the inhibitory effect of the isolated peptides on the activity of DPP-IV. Moreover, these three peptides inhibit DPP-IV by a competitive mechanism. The most potent peptide, tested in the in vitro experiments, was Glu III (0.45 kDa). This peptide showed a catalytic efficiency of 5.6 x 10-6 min-1, Km´= 0.75 mM and a Ki= 0.11 mg/mL. Results obtained from the acute administration of amaranth protein fractions in the in vivo experiments, showed that the protein fraction having the most positive effect on reducing postprandial glycaemia (around 26% higher compared to the control group) was the Glu fraction. When 300 mg Glu/kg were administer to the mice units (having a glucose oral charge of 2g/kg), the insulin released increased three times (1.2 ng/mL) and glucagon concentration fell 30% compared to the control units (p <0.05). Sub-acute administration (30 day period) of amaranth protein fractions showed that the Glu fraction was the most effective to decrease postprandial glucose up to 17%. The protein fraction also increased the insulin content to 2.25 ng/L in the in vivo units tested, however, no significant changes were found on plasma glucacon levels. Hydrolyzed amaranth protein extracts obtained from the Glu fraction by alcalase hydrolysis and under the conditions described in the present work, could be used to develop functional foods having an inhibitory effect on DPP-IV. These functional food ingredients could help to treat diabetes type 2 and improve the quality of life of patients suffering from this type of diabetes. Nowadays, amaranth is not considered as a high value-added crop. However, the identification and characterization of biomolecules with biological activity, like the ones reported in this work will help to make a better use of amaranth nutritional properties and to spread the cultivation of this plant.; El amaranto (Amaranthus hypochondriacus L) es un pseudocereal con un contenido de proteínas entre 16-20% mayor a los cereales comunes. Debido al gran contenido de proteínas, este pseudocereal ha sido objeto de estudio debido a las secuencias encriptadas con funcionalidad biológica. La hidrólisis enzimática libera biopéptidos a partir de proteínas; sin embargo, hay información limitada sobre la bioactividad de los péptidos de las proteínas de amaranto. Trabajos previos han mostrado por análisis in silico e in vitro que en las proteínas de este grano se encuentran encriptadas secuencias capaces de ejercer diversas actividades biológicas como: antihipertensiva, antioxidante, antitrombótica, anticancerígena y recientemente también se ha reportado capacidad para inhibir la enzima dipeptidil peptidasa IV (DPP-IV), enzima que se encuentra involucrada en la regulación de la glucemia posprandial. Tomando en cuenta los antecedentes respecto al potencial farmacológico que los hidrolizados del amaranto pueden tener, el objetivo del presente estudio fue evaluar la capacidad de diferentes fracciones proteínicas del grano de amaranto, para inhibir de forma in vitro e in vivo la DPP-IV, así como esclarecer la forma en la que estos péptidos realizan su proceso de inhibición con la finalidad de conocer la potencia de las fracciones, al mismo tiempo se caracterizaron fisicoquímicamente las fracciones peptídicas y purificaron de manera parcial los hidrolizados por cromatografía de filtración en gel, con la finalidad de evaluar la relación entre la inhibición de la DPP-IV y el peso molecular relativo, además de conocer la actividad de las fracciones seleccionadas se utilizó un modelo in vivo con ratones a los cuales se les indujo una diabetes por medio de STZ, donde se evaluó a través de una prueba oral de tolerancia a la glucosa, concentración de insulina y glucagón, evaluando el efecto durante una administración aguda y subaguda de los hidrolizados proteínicos. Se encontró tres principales fracciones proteínicas correspondientes a Alb1 46%, Glu 22%, Glo 12% y una fracción que representó una baja concentración Pro <1%, representando así el 83% de la proteína total del grano. La hidrólisis con alcalasa bajo las condiciones de tiempo y relación enzima/sustrato estudiadas en el presente trabajo mostró una hidrólisis extensiva de las proteínas donde la fracción que presentó mayor susceptibilidad al ataque proteolítico fue la fracción de Glu con un grado de hidrólisis de 75 ± 0.92% (24 h) y la fracción Alb1 fue la que presentó mayor resistencia al ataque proteolítico 43 ± 0.34% (48 h) con a una relación E/S de 0.8 UA/g. Los perfiles electroforéticos revelaron que la hidrólisis de las diferentes fracciones proteínicas reducía las proteínas de elevado peso molecular desde las primeras horas de tratamiento enzimático, también se encontraron proteínas que presentaron resistencia al ataque proteolítico específicamente entre 20-24 kDa, de ahí su bajo grado de hidrólisis. Durante la evaluación del porcentaje de inhibición de la DPP-IV, se encontró que los mayores tiempos de hidrólisis mostraban una mayor capacidad para inhibir la DPP-IV, encontrándose que la fracción de Glu alcanzó a las 24 h de tratamiento proteolítico una mayor capacidad para inhibir la DPP-IV 85  0.2% y para Alb1 y Glo de 48 h (45  0.2% y 63  0.5%, respectivamente). Los hidrolizados proteínicos que presentaron mayor grado de inhibición de la DPP-IV se purificaron parcialmente por cromatografía de exclusión molecular donde se encontró que las fracciones con pesos moleculares 0.86, 0.65 y 0.45 kDa (para Alb1, Glo y Glu; respectivamente) mostraron la mayor potencia para inhibir la DPP-IV, siendo los valores de IC50 de 1.98  0.01, 0.25  0.04 y 0.12  0.006 mg/mL, para las fracciones proteínicas antes mencionadas respectivamente, con lo cual se evidenció una relación inversa entre el peso molecular y la potencia para inhibir la DPP-IV. Se evaluó el comportamiento cinético de los inhibidores y se encontró que las tres fracciones proteínicas purificadas mostraron inhibición del tipo competitiva, la fracción con mayor potencia in vitro fue la fracción Glu.III (0.45 kDa) presentando un valor de Km´ 0.75 mM, eficiencia catalítica 5.6 x 10-6 min-1 y una constante de inhibición (Ki) de 0.11 mg/mL, esta fracción mostró que los péptidos generados por hidrólisis con alcalasa compiten con el sustrato por el sitio catalítico de la enzima, de forma in vitro. La evaluación de las distintas fracciones proteínicas con animales con diabetes inducida, en el estudio agudo, reveló que a diferencia de la evaluación in vitro la fracción que mostró un efecto positivo sobre la reducción en la glucemia posprandial (26% vs. el grupo control) fue la fracción Glu con una dosis de 300 mg/kg a los 30 min después de la administración de la carga oral de glucosa (2 g/kg), mostrando un aumento de insulina en tres veces (1.2 ng/mL) y una reducción en la concentración de glucagón en 30% comparado con el control (p <0.05). Para el estudio subagudo (administración durante 30 días) se demostró que al igual que en administración aguda la fracción Glu fue la que presentó un efecto positivo en la reducción de glucosa posprandial de 17%, a su vez los niveles de insulina aumentaron a 2.25 ng/mL, dos veces más altos que los encontrados en el estudio agudo, sin embargo no se encontraron cambios en los niveles plasmáticos de glucagón comparado con el respectivo control. Los hidrolizados obtenidos a partir de la fracción de Glu por digestión con alcalasa y bajo las condiciones aquí reportadas podrían ser utilizados para el desarrollo de alimentos funcionales con actividad inhibitoria de la DPP-IV podrían funcionar como coadyuvantes en el control de la diabetes mellitus tipo 2, con la finalidad de mejorar la calidad de vida de las personas que padecen la enfermedad. Hoy en día el amaranto no se considera un cultivo de alto valor agregado. Sin embargo, la identificación y caracterización de biomoléculas con actividad biológica, como las que se informan en el presente trabajo ayudaran a hacer un mejor uso de las propiedades nutricionales del amaranto e incentivar el cultivo de esta planta.